PERLINDUNGAN HUKUM TERHADAP GURU DALAM MENDIDIK SISWA BERDASARKAN UNDANG-UNDANG NOMOR 14 TAHUN 2005 TENTANG GURU DAN DOSEN STUDI DI SMP NEGERI 1 ONOLALU - Bago, Laurensia Dewi (JURNAL PANAH KEADILAN, 2025)
Legal Protection is a variety of legal efforts that must be provided by law enforcement officials to provide a sense of security; both mentally and physically from interference and various threats from any party. A teacher is a position or profession that requires special expertise in its main tasks such as educating, teaching, guiding, directing, training, assessing and evaluating students in early childhood education through formal education, primary and secondary education. The aim of this research is to find out how legal protection is for teachers in educating students based on Law Number 14 of 2005 concerning Teachers and Lecturers at SMP Negeri 1 Onolalu. The type of research used is sociological legal research, namely examining applicable legal provisions based on existing facts in a society. Data collection was carried out using primary data, secondary data and tertiary data. obtained from secondary legal materials. The data analysis used is qualitative data analysis. Qualitative data analysis is carried out together with the data collection process. Based on the research findings and discussion, it can be concluded that legal protection for teachers in educating students based on Law Number 14 of 2005 concerning Teachers and Study Lecturers at SMP Negeri 1 Onolalu is to provide guarantees for teachers to have the freedom to give sanctions to students if they violate the rules. , politeness norms and others. This is in line with the protection provided by SMP Negeri 1 Onolalu to teachers, namely that the school will provide protection to teachers if there are students who make punishment from the teacher a form of criminal act by resolving the problem amicably.